Rare earth zinc-aluminum alloy wire and production method thereof
By using cerium, gadolinium and scandium mixed rare earth elements and preparing anti-corrosion coatings in zinc-aluminum alloy wires, the problem of reduced corrosion life and easy breakage in high chloride ion environments has been solved, and the significant improvement has been achieved Effects of corrosion resistance, wear resistance and mechanical properties.
Patent Information
- Application Number
- CN202411532289.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-14
AI Technical Summary
The corrosion resistance life of zinc-aluminum alloy wires decreases in corrosion environments with high chloride ion content, and are easily broken when producing thin wires, so it needs to improve its corrosion resistance, wear resistance and mechanical properties. The single rare earth element cerium is added to the prior art and the content is relatively high, resulting in high processing costs and limited improvement in protection performance.
The rare earth elements composed of cerium, gadolinium and scandium are used to prepare alloy wire intermediates by melting, casting, extrusion, solid solution, aging and annealing treatment, and the anticorrosion coating is prepared by mixing polyols, isocyanates and other materials, and scraping them on the alloy The surface of the wire intermediate is dried to obtain a rare earth zinc-aluminum alloy wire.
It significantly improves the corrosion resistance, wear resistance, mechanical properties and stability of zinc-aluminum alloy wire, extends the service life, and has good overall overall performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of zinc-aluminum alloy wires, and in particular, relates to a rare earth zinc-aluminum alloy wire and a production method thereof. Background Art
[0002] With the development of modern industry, more and more mechanical equipment is required to operate stably for a long time under harsh working conditions. Therefore, it is necessary to improve the corrosion resistance and wear resistance of the material surface. Metal materials are prone to chemical and electrochemical reactions with the surrounding medium and suffer corrosion. Metal corrosion has caused serious damage to large steel structure buildings, affecting their safety and life. Thermal spraying metal coating is an important surface protection technology with good corrosion resistance and wear resistance. Commonly used thermal spraying metal coating materials on the market include zinc coating, aluminum coating and zinc-aluminum alloy wire. Its protection mechanism for metal materials: First, it has an isolation effect of blocking corrosive media similar to the anti-corrosion mechanism of paint coating; second, it is an anodic protection effect achieved through the self-sacrifice of coating materials. Thermal spraying metal coating materials have been widely used in coal mines, large civil steel structure buildings, bridges, high-speed railways, large ships, etc.
[0003] At present, the anti-corrosion life of zinc-aluminum alloy wire is significantly reduced in a corrosive environment with high chloride ion content, and it is easy to break when stretched during the production of thin wires. There is still a need to further improve its corrosion resistance, wear resistance and mechanical properties. In addition, rare earth elements are often added to increase the performance of zinc-aluminum alloy wire in the prior art, but most of them add a single rare earth element cerium, and the rare earth element content is also significantly high, resulting in high processing and manufacturing costs, affecting the improvement of the protective performance of the alloy wire and limiting its scope of application. Summary of the invention
[0004] The object of the present invention is to provide a rare earth zinc-aluminum alloy wire and a production method thereof, wherein the raw materials in step S1 are melted, then cast into round ingots, then extruded into thick wires, subjected to solid solution treatment, aging treatment and annealing treatment, and finally drawn into an alloy wire intermediate; the rare earth elements are composed of a mixture of cerium, gadolinium and scandium, and the three rare earth elements have good corrosion resistance and mechanical properties for the alloy; the tensile strength, hardness, ductility and other mechanical properties of the alloy wire intermediate can be further improved through solid solution treatment and aging treatment; polyol, isocyanate, alloy powder, reinforcing material, antioxidant, adhesion promoter, catalyst and filler are mixed, reacted, Finally, an anti-corrosion coating is obtained; the alloy powder is obtained by mixing a zirconium-based amorphous alloy and a titanium-based amorphous alloy and screening; the alloy powder can improve the corrosion resistance and mechanical properties of the polyurethane coating; the reinforcing material is prepared by modifying lanthanum oxide with nanoparticles and then grafting a silane coupling agent; the wear resistance and corrosion resistance of the alloy can be effectively improved; the anti-corrosion coating in step S3 is scraped onto the surface of the alloy wire intermediate in step S2, and then dried to obtain a rare earth zinc-aluminum alloy wire; the anti-corrosion coating can adhere well to the surface of the rare earth zinc-aluminum alloy wire, and can significantly improve the corrosion resistance, wear resistance, mechanical properties and stability of the zinc-aluminum alloy wire, and the overall comprehensive performance is good.
[0005] The technical problem to be solved by the present invention is as follows: the anti-corrosion life of zinc-aluminum alloy wire is significantly reduced in a corrosive environment with a high chloride ion content, and it is easy to break when stretched during the production of thin filaments, and its corrosion resistance, wear resistance and mechanical properties still need to be further improved; in addition, rare earth elements are often added to increase the performance of zinc-aluminum alloy wire in the prior art, but most of them add a single rare earth element cerium, and the rare earth element content is also significantly high, resulting in high processing and manufacturing costs, and affecting the improvement of the protective performance of the alloy wire, limiting its scope of application.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for producing rare earth zinc-aluminum alloy wire comprises the following steps: S1: Preparation: The materials include the following components by weight percentage: 20-30% aluminum, 0.2-0.5% magnesium, 0.1-0.3% tellurium, 0.1-0.2% manganese, 0.02-0.06% rare earth elements, impurities not exceeding 0.01%, and the balance zinc; S2: preparing an alloy wire intermediate: melting the raw materials in step S1, then casting them into round ingots, then extruding them into thick wires, subjecting them to solution treatment, aging treatment and annealing treatment, and finally drawing them into an alloy wire intermediate; S3: preparing the anti-corrosion coating: mixing the polyol, isocyanate, alloy powder, reinforcing material, antioxidant, adhesion promoter, catalyst and filler, reacting, and finally obtaining the anti-corrosion coating; S4: preparing zinc-aluminum alloy wire: applying the anti-corrosion coating in step S3 to the surface of the alloy wire intermediate in step S2, and then drying to obtain rare earth zinc-aluminum alloy wire; The reinforcing material is prepared by modifying lanthanum oxide with nanoparticles and then grafting a silane coupling agent.
[0007] Furthermore, in step S1, the rare earth element is composed of cerium, gadolinium, and scandium in a mass ratio of 0.8-1.2:0.5-0.7:0.2-0.4.
[0008] Furthermore, step S2 is specifically as follows: The raw materials in step S1 are heated to a molten state at 1550-1600°C, then cast into ingots, homogenized at 300-400°C for 8-10h, hot extruded at 400-450°C, and passed through a circular die to form a thick wire with a diameter of 3-6mm. After solution treatment, aging treatment and annealing treatment, the thick wire is finally drawn to stretch it to 1-2.5mm to make an alloy wire intermediate.
[0009] Furthermore, the solution treatment has a solution temperature of 530-550°C and a solution holding time of 0.5-1.5h; the aging treatment has an aging temperature of 180-200°C and an aging holding time of 7-9h; and the annealing treatment has an annealing temperature of 200-240°C and an annealing time of 3-4h.
[0010] Furthermore, step S3 is specifically as follows: The polyol and the isocyanate are mixed, and the mixture is stirred and reacted at 75-85°C for 0.5-1h to obtain component A; the alloy powder, the reinforcing material, the catalyst, the antioxidant, the adhesion promoter and the filler are mixed, and the mixture is ultrasonically dispersed at 20-30°C for 1-1.5h to obtain component B; component A is mixed with component B, and the mixture is stirred and reacted for 30-50min to finally obtain the anti-corrosion coating.
[0011] During the above reaction process, the polyol has hydroxyl groups at both ends, the isocyanate has isocyanate groups at both ends, and the reinforcing material has amino groups. The isocyanate groups in the isocyanate can react and combine with the hydroxyl groups in the polyol and the amino groups in the reinforcing material, respectively, to finally form a polyurethane anti-corrosion coating.
[0012] Furthermore, the mass ratio of the polyol to the isocyanate is 1.5-2.5:4.5-5.5.
[0013] Furthermore, the mass ratio of the alloy powder, the reinforcing material, the catalyst, the antioxidant, the adhesion promoter and the filler is 0.4-0.6: 0.8-1.2: 0.02-0.03: 0.05-0.07: 0.06-0.08: 0.1-0.2.
[0014] Furthermore, the polyol is composed of a mixture of hydroxypropyl-terminated polydimethylsiloxane and polyether glycol in a mass ratio of 0.5-0.7:0.3-0.5.
[0015] Furthermore, the isocyanate is a mixture of isophorone diisocyanate and triphenylmethane triisocyanate in a mass ratio of 0.7-0.8:0.4-0.5.
[0016] Furthermore, the alloy powder is prepared by mixing and grinding a zirconium-based amorphous alloy and a titanium-based amorphous alloy in a mass ratio of 0.3-0.4:0.5-0.6, and after screening, obtaining an alloy powder with a particle size of 40-50 μm.
[0017] Furthermore, the catalyst is dibutyltin dilaurate.
[0018] Furthermore, the antioxidant is at least one of antioxidant 1010, antioxidant 2246-S, and antioxidant 1024.
[0019] Furthermore, the adhesion promoter is 3-isocyanatepropyltriethoxysilane.
[0020] Furthermore, the filler is at least one of carbon black, nano-silicon dioxide and bentonite.
[0021] Furthermore, the preparation method of the reinforcing material comprises the following steps: A1: dissolving lanthanum sulfate octahydrate and citric acid in an ethanol solution, then adding nanoparticles, ultrasonically dispersing for 30-50 minutes, filtering, washing with deionized water, and then drying to obtain nanoparticle-modified lanthanum oxide; A2: Add the nanoparticle-modified lanthanum oxide to an ethanol solution, then add a silane coupling agent, stir at 45-55° C. for 2-3 hours, centrifuge for 10-15 minutes, filter, wash with ethanol, and finally dry to obtain a reinforced material.
[0022] In the above reaction process, in step A1, lanthanum sulfate octahydrate is dissolved in an ethanol solution to release lanthanum ions. Citric acid, as a chelating agent, can form a stable chelate with the lanthanum ions, which helps to prevent the agglomeration of the lanthanum ions. The nanoparticles can also coordinate or chelate with the citric acid, which helps to prevent the agglomeration of the nanoparticles by ultrasonic dispersion, and finally obtain nanoparticle-modified lanthanum oxide; in step A2, the nanoparticle-modified lanthanum oxide has hydroxyl groups, and the silane coupling agent is hydrolyzed to generate silicon hydroxyl groups, which can be combined with the hydroxyl groups in the nanoparticle-modified lanthanum oxide, and the silane coupling agent is grafted onto the nanoparticle-modified lanthanum oxide, and finally obtain a reinforced material.
[0023] Furthermore, in step A1, the mass ratio of the lanthanum sulfate octahydrate, citric acid, ethanol solution, and nanoparticles is 0.4-0.5: 0.46-0.5: 240-260: 0.9-1.1.
[0024] Furthermore, in step A1, the nanoparticles are composed of zinc oxide nanoparticles and titanium diboride nanoparticles mixed in a mass ratio of 0.6-0.8:0.3-0.5.
[0025] Furthermore, in step A2, the mass ratio of the nanoparticle-modified lanthanum oxide to the ethanol solution is 1-2:30-40.
[0026] Furthermore, in step A2, the silane coupling agent is composed of γ-aminopropyltriethoxysilane and 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane in a mass ratio of 0.5-0.7:0.3-0.5.
[0027] Furthermore, step S4 is specifically as follows: The anti-corrosion coating in step S3 is scraped onto the surface of the alloy wire intermediate in step S2, with a coating thickness of 100-120 μm, and then dried at 80-100° C. for 3-5 hours to finally obtain the rare earth zinc-aluminum alloy wire.
[0028] Beneficial effects of the present invention: (1) In the technical solution of the present invention, the raw materials in step S1 are melted, then cast into an ingot, and then extruded into a thick wire, and then subjected to a solid solution treatment, an aging treatment and an annealing treatment, and finally drawn to form an alloy wire intermediate; the raw materials in step S1 include aluminum, magnesium, tellurium, manganese, rare earth elements, impurities and zinc. The alloy elements of aluminum, magnesium, tellurium, manganese and zinc are combined together to have good corrosion resistance. The rare earth elements are composed of a mixture of cerium, gadolinium and scandium. These three rare earth elements have good corrosion resistance and mechanical properties for the alloy. Adding scandium can improve the strength of the alloy by reducing the grain size and solid solution strengthening mechanism; adding gadolinium can enhance the corrosion resistance and mechanical properties of the alloy; adding cerium can significantly improve the refining effect of the alloy, reduce impurities and defects in the alloy, improve the mechanical properties and corrosion resistance of the zinc-aluminum alloy, and can chelate with other elements such as zinc and aluminum to improve the stability of the material; through solid solution treatment and aging treatment, the mechanical properties of the alloy wire intermediate such as tensile strength, hardness, ductility, etc. can be further improved.
[0029] (2) In the technical scheme of the present invention, polyol, isocyanate, alloy powder, reinforcing material, antioxidant, adhesion promoter, catalyst and filler are mixed and reacted to finally obtain an anti-corrosion coating; wherein the alloy powder is obtained by mixing and grinding zirconium-based amorphous alloy and titanium-based amorphous alloy and then screening; zirconium-based amorphous alloy and titanium-based amorphous alloy are added to polyurethane to further improve the corrosion resistance of the polyurethane coating and have good mechanical properties; the reinforcing material is prepared by modifying lanthanum oxide with nanoparticles and then grafting a silane coupling agent; the zinc oxide nanoparticles and the diisocyanate are prepared by mixing and grinding the zinc oxide nanoparticles and the diisocyanate; the polyurethane coating is obtained by mixing and grinding the zinc oxide nanoparticles and the diisocyanate; the polyurethane coating is obtained by mixing and grinding the zinc oxide nanoparticles and the diisocyanate; the polyurethane coating is obtained by mixing and grinding the zinc oxide nanoparticles and the diisocyanate; the polyurethane coating is obtained by mixing and grinding the zinc oxide nanoparticles and the diisocyanate; the polyurethane coating is obtained by mixing and grinding the zinc oxide nanoparticles and the diisocyanate; the polyurethane coating is obtained by mixing and mixing ... Titanium boride nanoparticles are mixed to form nanoparticles, and then lanthanum oxide is modified, which can effectively improve the wear resistance and corrosion resistance of the alloy. The titanium diboride nanoparticles can refine the grain size, increase the thickness of the passivation film on the alloy surface, and effectively improve the corrosion resistance of the alloy; the anti-corrosion coating in step S3 is scraped onto the surface of the alloy wire intermediate in step S2, and then dried to obtain rare earth zinc-aluminum alloy wire; coating the anti-corrosion coating on the surface of the alloy wire intermediate not only has good adhesion, but also can significantly improve the corrosion resistance, wear resistance, mechanical properties and stability of the zinc-aluminum alloy wire.
[0030] (3) In the technical solution of the present invention, an alloy wire intermediate and an anti-corrosion coating are prepared separately, and then the anti-corrosion coating is coated on the surface of the alloy wire intermediate. After drying, a rare earth zinc-aluminum alloy wire is finally obtained; the prepared anti-corrosion coating can adhere well to the surface of the rare earth zinc-aluminum alloy wire, so that the rare earth zinc-aluminum alloy wire has better mechanical properties, corrosion resistance, wear resistance and stability, and extends its service life, and the overall comprehensive performance is good. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The specific parameters of the raw materials used in the present invention are as follows: Hydroxypropyl-terminated polydimethylsiloxane (HPMS, number average molecular weight of 1500, purchased from Sinopharm Chemical Reagent Co., Ltd.), dried at 110 °C before use; polyether diol (DL-2000D), provided by Shandong Bluestar Dongda Co., Ltd.; isophorone diisocyanate, CAS: 4098-71-9, provided by Shanghai MacLean Biochemical Co., Ltd.; triphenylmethane triisocyanate, CAS: 2422-91-5, provided by Shanghai Eon Chemical Technology Co., Ltd.; zinc oxide nanoparticles, average particle size of 50 nm; titanium diboride nanoparticles, average particle size of 50-100 nm; zirconium-based amorphous alloy, Zr41.2 Ti13.8 Cu12.5Ni10 Be22.5 (At%); titanium-based amorphous alloy, Ti75 Zr11 Si9 Fe5 (At%).
[0033] Example 1 The specific steps of preparing rare earth zinc aluminum alloy wire are as follows: S1: Preparation: The materials include the following components by weight percentage: 20% aluminum, 0.2% magnesium, 0.1% tellurium, 0.1% manganese, 0.02% rare earth elements, 0.007% impurities, and the balance is zinc, wherein the rare earth elements are composed of cerium, gadolinium, and scandium in a mass ratio of 0.8:0.5:0.2; S2: The raw materials in step S1 are heated to a molten state at 1550°C, then cast into an ingot, the ingot is homogenized at 300°C for 8 hours, then hot extruded at 400°C, and then passed through a circular die to form a thick wire with a diameter of 3 mm, and then subjected to solid solution treatment, aging treatment and annealing treatment, and finally drawn to stretch the thick wire to 1 mm to form an alloy wire intermediate, wherein the solid solution temperature is 530°C, the solid solution holding time is 1.5 hours; the aging temperature is 180°C, the aging holding time is 9 hours; the annealing temperature is 200°C, and the annealing time is 4 hours; S3: According to the mass ratio of polyol to isocyanate of 1.5:4.5, the polyol and isocyanate are mixed, and the mixture is stirred at 75°C and 600 rpm for 1 hour to obtain component A, and according to the mass ratio of alloy powder, reinforcing material, dibutyltin dilaurate, antioxidant 1010, 3-isocyanatepropyltriethoxysilane and carbon black of 0.4:0.8:0.02:0.05:0.06:0.1, the alloy powder, reinforcing material, dibutyltin dilaurate, antioxidant 1010, 3-isocyanatepropyltriethoxysilane and carbon black are mixed, Ultrasonic dispersion was performed at 20°C for 1 hour to obtain component B, component A was mixed with component B, and the mixture was stirred for reaction for 30 minutes to finally obtain an anti-corrosion coating, wherein the polyol was composed of a mixture of hydroxypropyl-terminated polydimethylsiloxane and polyether diol in a mass ratio of 0.5:0.3; the isocyanate was composed of a mixture of isophorone diisocyanate and triphenylmethane triisocyanate in a mass ratio of 0.7:0.4; the alloy powder was mixed and ground with a zirconium-based amorphous alloy and a titanium-based amorphous alloy in a mass ratio of 0.3:0.5, and after sieving, an alloy powder with a particle size of 40 μm was obtained; The method for preparing the reinforcing material comprises the following steps: A1: According to the mass ratio of lanthanum sulfate octahydrate, citric acid, ethanol solution and nanoparticles being 0.4:0.46:240:0.9, lanthanum sulfate octahydrate and citric acid are dissolved in 80wt% ethanol solution, and then nanoparticles are added, ultrasonically dispersed for 30 minutes, filtered, washed with deionized water (the mass of deionized water is 20wt% of the ethanol solution), and dried at 60°C for 24 hours to obtain nanoparticle-modified lanthanum oxide, wherein the nanoparticles are composed of zinc oxide nanoparticles and titanium diboride nanoparticles mixed in a mass ratio of 0.6:0.3; A2: According to the mass ratio of nanoparticle-modified lanthanum oxide to ethanol solution of 1:30, the nanoparticle-modified lanthanum oxide is added to a 75wt% ethanol solution, and then a silane coupling agent is added (the mass of the silane coupling agent is 30wt% of the nanoparticle-modified lanthanum oxide), stirred at 45°C for 2h, centrifuged at 6000rpm for 15min, filtered, washed with ethanol 3 times (the mass of each ethanol is 10 times the mass of the nanoparticle-modified lanthanum oxide), and finally dried for 24h to obtain a reinforced material, wherein the silane coupling agent is a mixture of γ-aminopropyltriethoxysilane and 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane in a mass ratio of 0.5:0.3; S4: Scrape the anti-corrosion coating in step S3 onto the surface of the alloy wire intermediate in step S2, with a coating thickness of 100 μm, and then dry at 80° C. for 5 hours to finally obtain a rare earth zinc-aluminum alloy wire.
[0034] Example 2 The specific steps of preparing rare earth zinc aluminum alloy wire are as follows: S1: Material preparation: In terms of weight percentage, the material comprises the following components: 25% aluminum, 0.4% magnesium, 0.2% tellurium, 0.15% manganese, 0.04% rare earth elements, 0.005% impurities, and the balance is zinc, wherein the rare earth elements are composed of cerium, gadolinium, and scandium mixed in a mass ratio of 1:0.6:0.3; S2: The raw materials in step S1 are heated to a molten state at 1580°C, and then cast into an ingot, the ingot is homogenized at 350°C for 9 hours, and then hot extruded at 435°C, and then passed through a circular die to form a thick wire with a diameter of 5 mm, and then subjected to solid solution treatment, aging treatment and annealing treatment, and finally drawn to stretch the thick wire to 2 mm to form an alloy wire intermediate, wherein the solid solution temperature is 540°C, the solid solution holding time is 1 hour; the aging temperature is 190°C, the aging holding time is 8 hours; the annealing temperature is 220°C, and the annealing time is 3.5 hours; S3: According to the mass ratio of polyol to isocyanate of 2:5, the polyol and isocyanate are mixed, and the reaction is stirred at 80°C and 700 rpm for 0.7h to obtain component A, and according to the mass ratio of alloy powder, reinforcing material, dibutyltin dilaurate, antioxidant 2246-S, 3-isocyanatepropyltriethoxysilane and nano-silica of 0.5:1:0.025:0.06:0.07:0.15, the alloy powder, reinforcing material, dibutyltin dilaurate, antioxidant 2246-S, 3-isocyanatepropyltriethoxysilane and nano-silica are mixed. The components A and B are mixed, ultrasonically dispersed at 25°C for 1.2 hours to obtain component B, component A is mixed with component B, and stirred for reaction for 40 minutes to obtain an anti-corrosion coating, wherein the polyol is composed of a mixture of hydroxypropyl-terminated polydimethylsiloxane and polyether diol in a mass ratio of 0.6:0.4; the isocyanate is composed of a mixture of isophorone diisocyanate and triphenylmethane triisocyanate in a mass ratio of 0.75:0.45; the alloy powder is a mixture of a zirconium-based amorphous alloy and a titanium-based amorphous alloy in a mass ratio of 0.35:0.55, and after sieving, an alloy powder with a particle size of 45 μm is obtained; The method for preparing the reinforcing material comprises the following steps: A1: According to the mass ratio of lanthanum sulfate octahydrate, citric acid, ethanol solution and nanoparticles being 0.45:0.48:250:1, lanthanum sulfate octahydrate and citric acid are dissolved in 80wt% ethanol solution, and then nanoparticles are added, ultrasonically dispersed for 40 minutes, filtered, washed with deionized water (the mass of deionized water is 20wt% of the ethanol solution), and dried at 65°C for 24 hours to obtain nanoparticle-modified lanthanum oxide, wherein the nanoparticles are composed of zinc oxide nanoparticles and titanium diboride nanoparticles mixed in a mass ratio of 0.7:0.4; A2: According to the mass ratio of nanoparticle-modified lanthanum oxide to ethanol solution of 1.5:35, the nanoparticle-modified lanthanum oxide is added to a 75wt% ethanol solution, and then a silane coupling agent is added (the mass of the silane coupling agent is 30wt% of the nanoparticle-modified lanthanum oxide), stirred at 50°C for 2.5h, centrifuged at 7000rpm for 13min, filtered, washed with ethanol 3 times (the mass of each ethanol is 10 times the mass of the nanoparticle-modified lanthanum oxide), and finally dried for 24h to obtain a reinforced material, wherein the silane coupling agent is a mixture of γ-aminopropyltriethoxysilane and 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane in a mass ratio of 0.6:0.4; S4: Scrape the anti-corrosion coating in step S3 onto the surface of the alloy wire intermediate in step S2, with a coating thickness of 110 μm, and then dry at 90° C. for 4 hours to finally obtain a rare earth zinc-aluminum alloy wire.
[0035] Example 3 The specific steps of preparing rare earth zinc aluminum alloy wire are as follows: S1: Preparation: The materials include the following components by weight percentage: 30% aluminum, 0.5% magnesium, 0.3% tellurium, 0.2% manganese, 0.06% rare earth elements, 0.01% impurities, and the balance is zinc, wherein the rare earth elements are composed of cerium, gadolinium, and scandium in a mass ratio of 1.2:0.7:0.4; S2: The raw materials in step S1 are heated to a molten state at 1600°C, and then cast into an ingot, the ingot is homogenized at 400°C for 10 hours, and then hot extruded at 450°C, and then passed through a circular die to form a thick wire with a diameter of 6 mm, and then subjected to solid solution treatment, aging treatment and annealing treatment, and finally drawn to stretch the thick wire to 2.5 mm to form an alloy wire intermediate, wherein the solid solution temperature is 550°C, the solid solution holding time is 0.5h; the aging temperature is 200°C, the aging holding time is 7h; the annealing temperature is 240°C, and the annealing time is 3h; S3: According to the mass ratio of polyol to isocyanate of 2.5:5.5, the polyol and isocyanate are mixed, and the reaction is stirred at 85°C and 800 rpm for 0.5 h to obtain component A, and according to the mass ratio of alloy powder, reinforcing material, dibutyltin dilaurate, antioxidant 1024, 3-isocyanatepropyltriethoxysilane and bentonite of 0.6:1.2:0.03:0.07:0.08:0.2, the alloy powder, reinforcing material, dibutyltin dilaurate, antioxidant 1024, 3-isocyanatepropyltriethoxysilane and bentonite are mixed. , ultrasonically disperse at 30°C for 1.5h to obtain component B, mix component A with component B, and stir to react for 50min to finally obtain an anti-corrosion coating, wherein the polyol is composed of a mixture of hydroxypropyl-terminated polydimethylsiloxane and polyether diol in a mass ratio of 0.7:0.5; the isocyanate is composed of a mixture of isophorone diisocyanate and triphenylmethane triisocyanate in a mass ratio of 0.8:0.5; the alloy powder is a mixture of zirconium-based amorphous alloy and titanium-based amorphous alloy in a mass ratio of 0.4:0.6, and after sieving, an alloy powder with a particle size of 50μm is obtained; The method for preparing the reinforcing material comprises the following steps: A1: According to the mass ratio of lanthanum sulfate octahydrate, citric acid, ethanol solution and nanoparticles being 0.5:0.5:260:1.1, lanthanum sulfate octahydrate and citric acid are dissolved in 80wt% ethanol solution, and then nanoparticles are added, ultrasonically dispersed for 50 minutes, filtered, washed with deionized water (the mass of deionized water is 20wt% of the ethanol solution), and dried at 70°C for 24 hours to obtain nanoparticle-modified lanthanum oxide, wherein the nanoparticles are composed of zinc oxide nanoparticles and titanium diboride nanoparticles mixed in a mass ratio of 0.8:0.5; A2: According to the mass ratio of nanoparticle-modified lanthanum oxide to ethanol solution of 2:40, the nanoparticle-modified lanthanum oxide is added to a 75wt% ethanol solution, and then a silane coupling agent is added (the mass of the silane coupling agent is 30wt% of the nanoparticle-modified lanthanum oxide), stirred at 55°C for 3h, centrifuged at 8000rpm for 10min, filtered, washed with ethanol 3 times (the mass of each ethanol is 10 times the mass of the nanoparticle-modified lanthanum oxide), and finally dried for 24h to obtain a reinforced material, wherein the silane coupling agent is a mixture of γ-aminopropyltriethoxysilane and 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane in a mass ratio of 0.7:0.5; S4: Scrape the anti-corrosion coating in step S3 onto the surface of the alloy wire intermediate in step S2, with a coating thickness of 120 μm, and then dry at 100° C. for 3 hours to finally obtain a rare earth zinc-aluminum alloy wire.
[0036] Comparative Example 1 The difference between this comparative example and Example 3 is that when preparing the rare earth zinc-aluminum alloy wire, the mass of the rare earth element in step S1 is replaced by a rare earth element composed of cerium and scandium mixed in a mass ratio of 1.2:1.1, and the remaining steps and raw materials are synchronized with Example 3; S1: Material preparation: Calculated by weight percentage, it includes the following components: 30% aluminum, 0.5% magnesium, 0.3% tellurium, 0.2% manganese, 0.06% rare earth elements, 0.01% impurities, and the balance is zinc. The rare earth elements are composed of cerium and scandium mixed in a mass ratio of 1.2:1.1.
[0037] Comparative Example 2 The difference between this comparative example and Example 3 is that when preparing the rare earth zinc-aluminum alloy wire, the mass of the rare earth elements in step S1 is replaced by a rare earth element composed of cerium, gadolinium, scandium, and lanthanum in a mass ratio of 1.2:0.7:0.2:0.2, and the remaining steps and raw materials are the same as those in Example 3; S1: Material preparation: Calculated by weight percentage, it includes the following components: 30% aluminum, 0.5% magnesium, 0.3% tellurium, 0.2% manganese, 0.06% rare earth elements, 0.01% impurities, and the balance is zinc. The rare earth elements are composed of cerium, gadolinium, scandium, and lanthanum mixed in a mass ratio of 1.2:0.7:0.2:0.2.
[0038] Comparative Example 3 The difference between this comparative example and Example 3 is that when preparing the rare earth zinc-aluminum alloy wire, no solid solution treatment and aging treatment are performed in step S2, and the remaining steps and raw materials are synchronized with Example 3; S2: The raw materials in step S1 are heated to a molten state at 1600°C, and then cast into an ingot. The ingot is homogenized at 400°C for 10 hours, and then hot extruded at 450°C, and then passed through a circular mold to form a thick wire with a diameter of 6 mm. After annealing, the thick wire is finally drawn to stretch it to 2.5 mm to make an alloy wire intermediate, wherein the annealing temperature is 240°C and the annealing time is 3 hours.
[0039] Comparative Example 4 The difference between this comparative example and Example 3 is that when preparing the anti-corrosion coating, the alloy powder in step S3 is replaced by grinding a zirconium-based amorphous alloy, and after screening, an alloy powder with a particle size of 50 μm is obtained, and the remaining steps and raw materials are synchronized with Example 3; S3: According to the mass ratio of polyol to isocyanate of 2.5:5.5, the polyol and isocyanate are mixed, and the reaction is stirred at 85°C and 800 rpm for 0.5 h to obtain component A, and according to the mass ratio of alloy powder, reinforcing material, dibutyltin dilaurate, antioxidant 1024, 3-isocyanatepropyltriethoxysilane and bentonite of 0.6:1.2:0.03:0.07:0.08:0.2, the alloy powder, reinforcing material, dibutyltin dilaurate, antioxidant 1024, 3-isocyanatepropyltriethoxysilane and bentonite are mixed. Ethoxysilane and bentonite are mixed, ultrasonically dispersed at 30°C for 1.5 hours to obtain component B, component A is mixed with component B, and stirred for reaction for 50 minutes to finally obtain an anti-corrosion coating, wherein the polyol is composed of a mixture of hydroxypropyl-terminated polydimethylsiloxane and polyether diol in a mass ratio of 0.7:0.5; the isocyanate is composed of a mixture of isophorone diisocyanate and triphenylmethane triisocyanate in a mass ratio of 0.8:0.5; the alloy powder is ground by a zirconium-based amorphous alloy, and after screening, an alloy powder with a particle size of 50 μm is obtained.
[0040] Comparative Example 5 The difference between this comparative example and Example 3 is that when preparing the reinforcing material, the mass of the nanoparticles in step A1 is replaced by zinc oxide nanoparticles, and the remaining steps and raw materials are the same as those in Example 3; A1: According to the mass ratio of lanthanum sulfate octahydrate, citric acid, ethanol solution and zinc oxide nanoparticles of 0.5:0.5:260:1.1, lanthanum sulfate octahydrate and citric acid were dissolved in 80wt% ethanol solution, and then zinc oxide nanoparticles were added and ultrasonically dispersed for 50 minutes. After filtration, the mixture was washed with deionized water (the mass of deionized water was 20wt% of the ethanol solution) and dried at 70°C for 24 hours to obtain nanoparticle-modified lanthanum oxide.
[0041] Comparative Example 6 The difference between this comparative example and Example 3 is that when preparing the reinforcing material, the mass of the silane coupling agent in step A2 is replaced by γ-aminopropyltriethoxysilane, and the remaining steps and raw materials are the same as those in Example 3; A2: According to the mass ratio of nanoparticle-modified lanthanum oxide and ethanol solution being 2:40, the nanoparticle-modified lanthanum oxide was added to a 75wt% ethanol solution, and then γ-aminopropyltriethoxysilane was added (the mass of γ-aminopropyltriethoxysilane was 30wt% of the nanoparticle-modified lanthanum oxide), stirred at 55°C for 3h, centrifuged at 8000rpm for 10min, filtered, washed with ethanol 3 times (the mass of ethanol each time was 10 times the mass of the nanoparticle-modified lanthanum oxide), and finally dried for 24h to obtain a reinforced material.
[0042] The rare earth zinc-aluminum alloy wires prepared in Examples 1-3 and Comparative Examples 1-6 are now tested for mechanical properties, corrosion resistance, and wear resistance; Corrosion resistance test: According to the GB / T 1771-2007 test standard, the rare earth zinc-aluminum alloy wires prepared in Examples 1-3 and Comparative Examples 1-6 are subjected to a neutral salt spray test to test their corrosion resistance; Wear resistance test: According to the GB / T 12444.1-1990 test standard, the rare earth zinc-aluminum alloy wires prepared in Examples 1-3 and Comparative Examples 1-6 are subjected to a wear volume test to test their wear resistance; Mechanical property test: The tensile strength test is performed according to the GB / T 228.1-2021 test standard, and the impact resistance test is performed according to the GB / T 1732-2020 test standard. The test results are shown in Table 1 below: Table 1 Performance parameters of rare earth zinc aluminum alloy wires prepared in Examples 1-3 and Comparative Examples 1-6
[0043] It can be seen from the data in Table 1 above that, by comparing Comparative Examples 1-2 with Example 3, it can be seen that the rare earth elements in step S1 are replaced by rare earth elements composed of cerium and scandium in a mass ratio of 1.2:1.1 or the rare earth elements in step S1 are replaced by rare earth elements composed of cerium, gadolinium, scandium and lanthanum in a mass ratio of 1.2:0.7:0.2:0.2 to prepare rare earth zinc-aluminum alloy wire, and the test results thereof are worse than those in Example 3, indicating that the rare earth elements composed of cerium, gadolinium and scandium in a mass ratio of 1.2:0.7:0.4 are added to the alloying elements, which can not only improve the corrosion resistance and wear resistance of the zinc-aluminum alloy wire, but also have a good effect on the mechanical properties of the zinc-aluminum alloy wire; From the comparison between Comparative Example 3 and Example 3, it can be seen that the test result of preparing rare earth zinc-aluminum alloy wire in step S2 without solution treatment and aging treatment is poorer than that in Example 3, indicating that after the raw material in step S1 is prepared into coarse wire, further solution treatment, aging treatment and annealing treatment can improve the mechanical properties and wear resistance of the zinc-aluminum alloy wire, and also have a good effect on the corrosion resistance of the alloy wire; From the comparison between Comparative Example 4 and Example 3, it can be seen that the alloy powder in step S3 is replaced by the alloy powder with a particle size of 50 μm obtained by grinding the zirconium-based amorphous alloy and sieving to prepare the rare earth zinc-aluminum alloy wire. The test result is worse than that of Example 3, indicating that the alloy powder with a particle size of 50 μm obtained by mixing and grinding the zirconium-based amorphous alloy and the titanium-based amorphous alloy in a mass ratio of 0.4:0.6 and sieving is added to the polyurethane coating, which can effectively improve the corrosion resistance and mechanical properties of the coating, thereby further improving the mechanical properties, corrosion resistance and wear resistance of the zinc-aluminum alloy wire. By comparing Comparative Examples 5-6 with Example 3, it can be seen that when the mass of the nanoparticles in Step A1 is replaced by zinc oxide nanoparticles or the mass of the silane coupling agent in Step A2 is replaced by γ-aminopropyltriethoxysilane to prepare rare earth zinc-aluminum alloy wire, the test results are worse than those of Example 3, indicating that the nanoparticles composed of zinc oxide nanoparticles and titanium diboride nanoparticles mixed in a mass ratio of 0.8:0.5, then modified with lanthanum oxide, and then grafted with a silane coupling agent can not only improve the dispersibility of the nanoparticles and lanthanum oxide, effectively improve the corrosion resistance of the polyurethane coating, but also further improve the corrosion resistance, mechanical properties and wear resistance of the zinc-aluminum alloy wire.
[0044] It can be seen from Table 1 above that the rare earth zinc-aluminum alloy wires prepared in Examples 1-3, compared with the rare earth zinc-aluminum alloy wires prepared in Comparative Examples 1-6, meet the test performance requirements by preparing an alloy wire intermediate and an anti-corrosion coating, respectively, and then coating the anti-corrosion coating on the surface of the alloy wire intermediate, and finally obtaining the rare earth zinc-aluminum alloy wire after drying, while the rare earth zinc-aluminum alloy wires prepared in Comparative Examples 1-6 do not meet the performance requirements. This shows that the rare earth zinc-aluminum alloy wires prepared in the present invention not only have good mechanical properties, corrosion resistance and wear resistance, but also extend their service life and have good overall comprehensive performance.
[0045] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0046] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for producing rare earth zinc-aluminum alloy wire, characterized in that: The following steps are involved: S1: Preparation: The materials include the following components by weight percentage: 20-30% aluminum, 0.2-0.5% magnesium, 0.1-0.3% tellurium, 0.1-0.2% manganese, 0.02-0.06% rare earth elements, impurities not exceeding 0.01%, and the balance zinc; S2: preparing an alloy wire intermediate: melting the raw materials in step S1, then casting them into round ingots, then extruding them into thick wires, subjecting them to solution treatment, aging treatment and annealing treatment, and finally drawing them into an alloy wire intermediate; S3: preparing the anti-corrosion coating: mixing the polyol, isocyanate, alloy powder, reinforcing material, antioxidant, adhesion promoter, catalyst and filler, reacting, and finally obtaining the anti-corrosion coating; S4: preparing zinc-aluminum alloy wire: applying the anti-corrosion coating in step S3 to the surface of the alloy wire intermediate in step S2, and then drying to obtain zinc-aluminum alloy wire; The reinforcing material is prepared by modifying lanthanum oxide with nanoparticles and then grafting a silane coupling agent.
2. The method for producing a rare earth zinc-aluminum alloy wire according to claim 1, characterized in that: In step S1, the rare earth element is composed of cerium, gadolinium and scandium in a mass ratio of 0.8-1.2:0.5-0.7:0.2-0.
4.
3. The method for producing a rare earth zinc-aluminum alloy wire according to claim 1, characterized in that: Step S2 is specifically as follows: The raw materials in step S1 are heated to a molten state at 1550-1600°C, then cast into ingots, homogenized at 300-400°C for 8-10h, hot extruded at 400-450°C, and passed through a circular die to form a thick wire with a diameter of 3-6mm. After solution treatment, aging treatment and annealing treatment, the thick wire is finally drawn to stretch it to 1-2.5mm to make an alloy wire intermediate.
4. The method for producing a rare earth zinc-aluminum alloy wire according to claim 3, characterized in that: The solution treatment has a solution temperature of 530-550°C and a solution holding time of 0.5-1.5h; the aging treatment has an aging temperature of 180-200°C and an aging holding time of 7-9h; and the annealing treatment has an annealing temperature of 200-240°C and an annealing time of 3-4h.
5. The method for producing a rare earth zinc-aluminum alloy wire according to claim 1, characterized in that: Step S3 is specifically as follows: The polyol and the isocyanate are mixed, and the mixture is stirred and reacted at 75-85°C for 0.5-1h to obtain component A; the alloy powder, the reinforcing material, the catalyst, the antioxidant, the adhesion promoter and the filler are mixed, and the mixture is ultrasonically dispersed at 20-30°C for 1-1.5h to obtain component B; component A is mixed with component B, and the mixture is stirred and reacted for 30-50min to finally obtain the anti-corrosion coating.
6. The method for producing a rare earth zinc-aluminum alloy wire according to claim 5, characterized in that: The alloy powder is prepared by mixing and grinding a zirconium-based amorphous alloy and a titanium-based amorphous alloy in a mass ratio of 0.3-0.4:0.5-0.6, and then sieving to obtain an alloy powder with a particle size of 40-50 μm.
7. The method for producing a rare earth zinc-aluminum alloy wire according to claim 1, characterized in that: The preparation method of the reinforcing material comprises the following steps: A1: dissolving lanthanum sulfate octahydrate and citric acid in an ethanol solution, then adding nanoparticles, ultrasonically dispersing for 30-50 minutes, filtering, washing with deionized water, and then drying to obtain nanoparticle-modified lanthanum oxide; A2: Add the nanoparticle-modified lanthanum oxide to an ethanol solution, then add a silane coupling agent, stir at 45-55° C. for 2-3 hours, centrifuge for 10-15 minutes, filter, wash with ethanol, and finally dry to obtain a reinforced material.
8. The method for producing a rare earth zinc-aluminum alloy wire according to claim 7, characterized in that: In step A1, the nanoparticles are composed of zinc oxide nanoparticles and titanium diboride nanoparticles mixed in a mass ratio of 0.6-0.8:0.3-0.
5.
9. The method for producing a rare earth zinc-aluminum alloy wire according to claim 1, characterized in that: Step S4 is specifically as follows: The anti-corrosion coating in step S3 is scraped onto the surface of the alloy wire intermediate in step S2, with a coating thickness of 100-120 μm, and then dried at 80-100° C. for 3-5 hours to finally obtain the rare earth zinc-aluminum alloy wire.
10. A rare earth zinc-aluminum alloy wire obtained by the preparation method according to any one of claims 1 to 9.